2022
DOI: 10.56093/ijans.v92i12.128220
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of growth curve in farm bred broiler rabbits in organized rabbitry

Abstract: Rabbit rearing across the Indian subcontinent is growing rapidly. Growth traits are important parameters on which rabbits are being evaluated. Mathematical models have been tried to establish a relationship between body weight and time. Data spread over six years on the weekly body weight of Soviet Chinchilla and White Giant rabbits were collected and subjected to analysis for assessment of genetic parameters and factors which influence the weekly body weight. Three nonlinear growth models; Gompertz, Logistic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
0
1
1
Order By: Relevance
“…The growth parameters reported using the logistic model for Soviet Chinchilla and White Giant rabbits were higher than the estimated values of A, B, and K in this study (ranges of 476.06-943.35, 9.55-13.14, and 0.06-0.08, respectively) (Gupta et al, 2022). Comparing the estimated IA and IW for LL and FF animals, using the Gompertz model reported by Setiaji et al (2013), revealed that the estimates for FF animals were lower (41.76 and 465.21 g, respectively), whereas the estimates for LL rabbits were slightly higher (29.69 and 238.03 g, respectively).…”
Section: Discussioncontrasting
confidence: 84%
“…The growth parameters reported using the logistic model for Soviet Chinchilla and White Giant rabbits were higher than the estimated values of A, B, and K in this study (ranges of 476.06-943.35, 9.55-13.14, and 0.06-0.08, respectively) (Gupta et al, 2022). Comparing the estimated IA and IW for LL and FF animals, using the Gompertz model reported by Setiaji et al (2013), revealed that the estimates for FF animals were lower (41.76 and 465.21 g, respectively), whereas the estimates for LL rabbits were slightly higher (29.69 and 238.03 g, respectively).…”
Section: Discussioncontrasting
confidence: 84%
“…Світовий попит на кролятину зростає з року в рік [1], оскільки цей цінний і корисний продукт має важливе економічне значення -здатен суттєво забезпечити попит на м'ясну продукцію. Проте існує дуже обмежена кількість досліджень швидкості росту кролів, у яких розглядається ефект генетичних і негенетичних факторів [2].…”
unclassified